Environmental Heat Stress Among Young Working Women: A Pilot Study - Juma Rahman; S.H.M. Fakhruddin; A.K.M. Fazlur Rahman; M.A. Halim (Ubiquity Press, 2017)
Background Heat waves are increasing significantly in frequency and severity and threaten the health and income of outdoor workers. Pregnant women workers are particularly at risk due to their delicate physiological systems and accountabilities to future generations. Animal and human studies propose that elevated body temperatures during pregnancy can induce adverse pregnancy outcomes. Objective To measure the change in internal body temperature (Tcore) in young working women before, after, and during work (both outdoor and indoor) on hot humid days and relate threshold temperature to the upshot adverse effects of pregnancy (teratogenicity and related miscarriage). Methods Tympanic temperatures were measured using infrared ear thermometers and workplace temperatures were collected using Lascar Data Logger. Brief exploratory interviews were conducted to gather qualitative data, and content analysis was also carried out. Findings Body temperatures were found elevated among outdoor women workers compared with that of indoor women workers. Conclusions The present study found that outdoor work during pregnancy in hot, humid days might increase body temperature up to levels that could induce fetal destruction or anomaly.